What do we know about police leadership? A review of the current status of police leadership research and practice, with suggestions for future research directions - Filstad, Cathrine (Policing and society, 2025)
This article, which consists of three systematic reviews covering the period 1992–2023, focuses on why scholarly knowledge of effective police leadership is limited. The literature on police leadership amounts to just 197 peer-reviewed journal articles; most of these are leader-centric and tend to uncritically echo the conventional literature, focusing on police leaders` traits and styles as independent of context and practice. Using three surveys of peer-reviewed journal articles and a sample of around ten contributions to the contemporary critical leadership literature on police leadership research, we make a series of recommendations for future directions. Firstly, the collective and relational nature of police leadership, which is understood to be a co-production involving leaders and followers, is under-researched. Secondly, studies are needed to narrow the gap between leadership theories and police leadership practice and recognise the need for research on what works or does not work. Thirdly, conceptual parameters and their effects on police leadership, particularly organisational, structural, and hierarchical conditions, should be examined in more detail. Each suggestion highlights the socially constructed, situated, relational processes and practice-orientated nature of leadership, which is essential if future research is to be relevant to police forces.